PEMBUATAN SARANA UNTUK PAPAN PETUNJUK JALAN DI DESA MLANDINGAN WETAN - Setiowati, Erika; Daynuri, Ahmad; Sholeh, Fajar; Amin, Lutfil; Sayyinul, Sayyinul; Fauzi, Muhammad; Jannah, Raudatul (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2024)
The problem that occurs in several villages is that there are no road signs at several points on the road. This problem also occurs in Mlandingan Wetan village in Situbondo Regency. Several problems need to be addressed and every settlement requires many panels or street signs. Signboards and road signs must also be installed to help new arrivals access Mlandingan Wetan Village. This charity activity began with a direct visit to the location where the billboards were installed. After finding a place to install the plaque, the next step is to buy the tools and materials needed to make the plaque or plaque. After the signboards were finished, they continued with painting, then PBPMD members assisted by local residents made the names with 6 plaques produced. This activity was carried out in Mlandingan Wetan Village in 6 villages, namely Klowangan Village, Palongan Village, Pesisir Village, Krajan Village, La'angan Village and Tegal China Village. Thanks to the help and cooperation of all village residents, we were able to complete this project successfully. Because it is important to make traffic signs. This is all thanks to the support of the local community. There are no obstacles in preparing, implementing and evaluating this activity, it only adds time to the process. Making and installing these boards is a form of involvement, coordination and active participation of students, teachers and the community.